Pemanfaatan E-Commerce Sebagai Strategi Pemasaran Produk UMKM di Desa Widarapayung Wetan Kabupaten Cilacap - Ayu Pramita; Rosita Dwityaningsih; Saipul Bahri; Taufan Ratri Harjanto; Niki Tri Utami; Meita Nuranggraeni (Kreativasi : Journal of Community Empowerment, 2022)
The implementation of this community service involves one partner, namely the “Tunggal Makmur” MSME Group. This partner is located in Widarapayung Wetan Village, Cilacap Regency, which is about 43.2 km from Cilacap State Polytechnic. This group has various businesses, including various vegetable chips, fried onions and red ginger ready to brew. The purpose of implementing this community service is to apply e-commerce to the sale of various MSME products in Widarapayung Wetan Village with the aim of introducing and increasing sales turnover, while the method used is by using participatory methods, counseling, mentoring and training. The results obtained from the implementation of this community service are that with the assistance of training and e-commerce applications, it can increase the motivation for partners to carry out marketing of their products so that their turnover increases.